Effect of a novel in-office bleaching product with low hydrogen peroxide concentration: efficacy and side effects - Baranda, Maria João Matos Simão (2023)
Trabalho Final do Mestrado Integrado em Medicina Dentária apresentado à Faculdade de Medicina